(untitled) (Brazilian Journal of Oceanography, 2011)
In this stakeholder analysis related to the artificial reef (AR) program located in the Algarve (Southern Portugal mainland) 21 different stakeholder clusters were identified. Stakeholders were classified as primary, secondary and external. It was found that stakeholder interaction with the structures can be of private, public or cooperative interest. In the analysis there were also identified and mapped the impact of the program on stakeholders and their power to influence the ARs' outcomes. Stakeholders' interactions with the ARs were studied, along with their likely attitudes and behavior towards the man-made structures. Finally, all stakeholder clusters were classified according to their expected degree of involvement throughout the different AR stages. The purpose of this stakeholder analysis was to find out winners and losers connected with the reef deployment. It was found that most stakeholder clusters were affected positively, but also four clusters affected negatively. However, it is believed that those that may be affected negatively do not pose a serious threat to the expected AR development along its lifetime.